Book Review: Islamic Law in Saudi Arabia, by Dominik Krell, Leiden, Boston, Brill, 2025, 236 pp., € 89,00 (hardback), ISBN 978-90-04-68328-0, ISBN 978-90-04-72631-4 (e-book) - Ibtihaj M. Zafeiris; Ayeza Hajra Mazari (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2025)
Dominik Krell’s Islamic Law in Saudi Arabia offers an incisive exploration of how the Saudi legal system negotiates the tension between divine authority and state control. Moving beyond the simplistic binaries of “traditional versus modern”, the book situates Islamic law as a discursive tradition shaped by jurists, judges, and state institutions. Krell traces the evolution of siyāsah sharʿiyyah, the codification debates, and the narrowing of ijtihād, showing how Saudi jurists mediate between the Hanbali school and contemporary reforms, including the 2022 Family Code. His use of court decisions, interviews, and archival sources provides a rare empirical depth. The book’s strength lies in demonstrating how orthodoxy is produced through power and discourse, while its limitation is the under-representation of marginalised voices, such as women and Shia scholars. This work significantly contributes to Islamic legal studies, comparative law, and debates on law-state relations in Muslim societies.